Effect of Orthodontic Bracket Base Structure on Shear Bond Strength - Faruk Ayhan Başçiftçi; Serdar Üşümez; Sıddık Malkoç; Metin Orhan (Galenos Yayinevi, 2006)
Direct bonding is the method of choice for attaching fixed orthodontic appliances. These fixed appliances are produced with various bonding bases. The present study aims to compare shear bond strengths (SBS) and fracture characteristics of the bracket adhesive interface of six different bracket base types. Standard mesh base (Ultraminitrim-Dentaurum, Germany), Supermesh base (Microarch- GAC, USA ), Integral base (Dyna-Lock, 3M Unitek, USA and Micro -loc GAC, USA), Micro-etched base (Mi -niature Twin, 3M-Unitek), and laser structured base (Discovery-Dentaurum, Germany) brackets were used. Twenty brackets of each type were bonded to specially constructed 120 bonding bases with Transbond XT (3M Unitek, USA). A testing machine (Model 500, Testometric, Lancashire, England) was used to evaluate shear bond strengths for all groups. After debonding, the amount of residual adhesive on the bracket was assessed according to the adhesive remnant index (ARI). ANOVA revealed statistically significant differences among the 6 groups tested (P<0.05). According to the results of Duncan's test highest SBS was achieved by laser treated Discovery brackets. This was followed by Micro-loc and Miniature Twin brackets. The SBS achieved by the latter two were lower but the difference with laser structured Discovery was statistically insignificant. The lowest SBS was achieved by Microarch bracket. From the results obtained in our study, we suggest that differences in bracket base design may lead to significant differences in shear bond strengths. Micro-loc, Miniature Twin or Discovery bases may be preferred to achieve higher shear bond strengths values and to reveal more accurate resin-enamel bond strength values in bond strength studies.